Women's education and family behavior trends in marriage, divorce and fertility - Isen, Adam; Stevenson, Betsey (CESifo working papers, 2010)
This paper examines how marital and fertility patterns have changed along racial and educational lines for men and women. Historically, women with more education have been the least likely to marry and have children, but this marriage gap has eroded as the returns to marriage have changed. Marriage and remarriage rates have risen for women with a college degree relative to women with fewer years of education. However, the patterns of, and reasons for, marriage have changed. College educated women marry later, have fewer children, are less likely to view marriage as "financial security", are happier in their marriages and with their family life, and are not only the least likely to divorce, but have had the biggest decrease in divorce since the 1970s compared to women without a college degree. In contrast, there have been fewer changes in marital patterns by education for men.